2001
DOI: 10.1038/sj.bmt.1702873
|View full text |Cite
|
Sign up to set email alerts
|

MC1288, a vitamin D analog, prevents acute graft-versus-host disease in rat bone marrow transplantation

Abstract: Summary:The major obstacle to successful bone marrow transplantation (BMT) is graft-versus-host disease (GVHD). Vitamin D analogs have shown their efficacy in solid organ transplantation. The purpose of this study was to investigate the suitability of a novel vitamin D analog, MC1288, in the prevention of acute GVHD in a rat BMT model. Allogeneic BMT were performed from Lewis to BN rats (n = 18). The animals were divided into four groups: an untreated control group, MC1288, cyclosporin A (CsA), and MC1288 + Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 10 publications
(13 reference statements)
0
26
0
7
Order By: Relevance
“…55 In allogeneic HSCT, the use of a vitamin D analog, MC 1288, has been shown to prevent acute GvHD in a rat model. 56 Middleton et al 57 in a study with 88 transplant recipients and 80 of their sibling donors, found that the ApaI allele when present in the patients' genotype was associated with severe acute GVHD. Analysis of donor polymorphisms found that survival was substantially lower in patients' receiving grafts from ApaI AA donors.…”
Section: Discussionmentioning
confidence: 99%
“…55 In allogeneic HSCT, the use of a vitamin D analog, MC 1288, has been shown to prevent acute GvHD in a rat model. 56 Middleton et al 57 in a study with 88 transplant recipients and 80 of their sibling donors, found that the ApaI allele when present in the patients' genotype was associated with severe acute GVHD. Analysis of donor polymorphisms found that survival was substantially lower in patients' receiving grafts from ApaI AA donors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin D analogues can prolong graft survival and prevent GVHD in animal studies. 51,52 Polymorphism in the VDR intron 8 region 53 and in intron 1 of the estrogen receptor alpha (ERα) 54 genes have been associated with both occurrence of GVHD and likelihood of survival following allo-BMT. In HLA-matched sibling BMT 53 the Apo1 "a" VDR allele in the patient was associated with severe acute GVHD, but with improved survival if present in the donor.…”
Section: Other Non-hla-encoded Genes Implicated Inmentioning
confidence: 99%
“…Accordingly, it has been shown that vitamin D analogs prevent acute GvHD in rat BMT and that the VDR gene polymorphism associates with GvHD and survival. 4,5 Up to now, no data are available on the endogenous serum levels of vitamin D metabolites during the course of BMT. In this study we measured 25-hydroxyvitamin D 3 (25(OH)D 3 ) and 1,25(OH) 2 D 3 in consecutive serum samples of 48 patients before and after allogeneic BMT.…”
mentioning
confidence: 99%